METHODS USED IN DETERMINING THE VALUE ADDED USED IN THE ASSESMENT OF THE COMPANY’S REAL ECONOMIC POWER - CONSTANTIN CĂRUNTU; MIHAELA LOREDANA LĂPĂDUŞI (Annals of the University of Petrosani: Economics, 2012)
When analyzing the value of a product or service, our goal is to obtain a product or service value that exceeds the cost of producing the good or service provision. Their cost includes the value of all resources used in its production, so it is necessary to examine each activity or resources involved in making a product or providing a service. Value added is the indicator that measures the economic performance of an economic entity which has a fairly long history of application at both micro and macro level. The purpose of this article is to set out the determination of the value added of a company through the synthetic and analytical method considered to be methods of determining the increasing level of the wealth of a business and of measuring the income. The research methodology used consists in the application of the two methods for determining the value added, the synthetic and analytical method, and also the use of the factorial method to reveal the factors of influence on value added.